Electrogenic and hydrocarbonoclastic biofilm at the oil-water interface as microbial responses to oil spill. (1st June 2021) - D'Ugo, Emilio; Bertuccini, Lucia; Spadaro, Francesca; Giuseppetti, Roberto; Iosi, Francesca; Santavenere, Fabio; Giuliani, Fausto; Gricia, Massimo; Rodomonte, Andrea; Lovecchio, Nicola; Mukherjee, Arghya; Bucci, Paola; et al.
Highlights: An Electrogenic and hydrocarbonoclastic biofilm as response to oil spill Biofilm microbes are involved in electrogenic and hydrocarbonoclastic activity Biofilm was connected to bacterial filaments to transfer electrons at distance Electrogenic filamentation was associated to "myelin like" expression pattern A vertical and spontaneous Liquid Microbial Fuel Cell (L-MFC) was created Abstract: The oil-water interface formed during an oil spill represents a challenging environment for pelagic communities living in aquatic ecosystems. At this anoxic barrier, we report the formation of a microbial hydrocarbonoclastic biofilm capable of electron transfer along the water column. This biofilm generated a membrane of surface-active compounds that allowed the spontaneous separation of electrical charges, causing the establishment of an anodic and a cathodic region and, as a result, the spontaneous creation of a liquid microbial fuel cell. Such floating biofilm was connected to the water column underneath by floating filaments that could contribute to oxygen reduction at distance. The filaments revealed an unusual lipid content induced by anoxic conditions, with prominent ultrastructural features similar to myelin found in oligodendrocytes of the vertebrate nervous system. Furthermore, these filaments showed an interesting cross-reactivity towards different epitopes of the myelin basic protein (MBP) and Claudin 11 (O4 ) of human oligodendrocytes. The presence of a network of filaments similar to myelin suggests the probable existence of evolutionary connections between very distant organisms. Collectively these results suggest a possible mechanism for how lake microbial communities can adapt to oil spills while offering an interesting starting point for technological developments of liquid microbial fuel cells related to the study of hydrocarbon-water interfaces. The data that support the findings of this study are openly available in figshare at https://figshare.com/s/72bc73ae14011dc7920d . Graphical abstract: Image, graphical abstract